Walking down the street: how does the built environment promote physical activity? A case study of Indonesian cities - Irfani Fithria Ummul Muzayanah; Ashintya Damayati; Kenny Devita Indraswari; Eldo Malba Simanjuntak; Tika Arundina (International Journal of Urban Sustainable Development, 2022)
This research merges individual self-reported physical-activity data from the fifth wave of the Indonesia Family Life Survey (IFLS) with data on Indonesian cities’ and municipalities’ built environments and employs cross-sectional multilevel regression to disentangle the relevant factors that affect individual incentives to engage in physical activity. The results suggest that high-density settings and land-use diversity in Indonesian urban settings adversely affect the incentive to engage in physical activity. Our finding reflects the common case of developing countries where the main problem arises from insufficient urban planning, which further results in other issues such as conventional land use and low-level safety and security. Thus, the result implies the urgency to improve built-environment planning in Indonesia to create a more supportive living environment that encourages residents to be more physically active, hence creating a healthier society.